VD_FINDINFO ACH 10/11 - 18/2011 vom 9. März 2011 - VD Tribunal cantonal (2011)
DROIT D'OBTENIR UNE DÉCISION, PROCÈS DEVENU SANS OBJET, RADIATION DU RÔLE | 29 al. 1 Cst., 56 al. 2 LPGA, 94 al. 1 let. c LPA-VD